A highly sensitive and versatile chiral sensor based on a top-gate organic field effect transistor functionalized with thiolated β-cyclodextrin. Issue 8 (5th March 2019) - Wang, Xuepeng; Wang, Yong; Wu, Yifan; Xiao, Yin
Abstract : A chiral sensor was successfully constructed by modifying an OFET gate with SH-β-CD. Abstract : The discrimination of chirality by field effect transistors (FETs) is a great challenge because enantiomers possess exactly identical charge and hence chiral recognition is solely related to spatial effects, while the working principle of most FET sensors is based on the intrinsic charge of analytes. In this work, a chiral organic field effect transistor (COFET) with a self-assembled thiolated β-cyclodextrin (SH-β-CD) monolayer modified gold top-gate electrode is developed to afford rapid, highly sensitive and real-time chiral discrimination for various enantiomers. Well-defined sensing results are achieved for diverse acidic enantiomers with the lowest detection concentration (LDC) of 10 −12 M. Chiral sensing mostly depends on the changed work function of the top electrode and hence varied surface potential at the gate/solution interface caused by the target-induced CD-enantiomer complex formation with different geometries for each isomer, which is independent of the intrinsic charge of the analytes. This proof-of-concept allows chiral resolution even for uncharged enantiomers, which still remains as a major hurdle for FET-based sensors. Furthermore, the COFET shows composition dependence for its response towards the enantiomer mixture of phenylalanine (Phe) and a "real world" pharmaceutical drug (ibuprofen), which proves the potentiality of the COFET for quantitative chiral analysis of commercial pharmaceutical drugs.